A Method for Demonstrating Superluminal Communication Using Conscious Intent to Influence a Quantum-Entangled Link - Wilkinson, Walter John (Journal of Scientific Exploration, 2023)
It is fair to say that Bell's Theorem leaves a nasty taste in the mouths of many physicists because test results seem to suggest that non-local, i.e., superluminal, communication of some sort is going on all around us and maybe not just at the quantum level. But Bell's Theorem has been aptly demonstrated to date, and Quantum Mechanics (QM) is, if not the most successful theory devised by man, certainly one of them. To some, and especially to Einstein, one of the least favorable aspects of QM is its statistical nature. This paper embraces QM's statistical nature and employs quantum entanglement to show that superluminal communication may be possible, albeit, most likely, initially, at a very low bit rate.